Health informatics competencies in postgraduate medical education and training in the UK: a mixed methods study. Issue 3 (30th March 2019) - Jidkov, Lydia; Alexander, Matthew; Bark, Pippa; Williams, John G; Kay, Jonathan; Taylor, Paul; Hemingway, Harry; Banerjee, Amitava
Abstract : Objective: To assess health informatics (HI) training in UK postgraduate medical education, across all specialties, against international standards in the context of UK digital health initiatives (eg, Health Data Research UK, National Health Service Digital Academy and Global Digital Exemplars). Design: A mixed methods study of UK postgraduate clinician training curricula (71 specialties) against international HI standards: scoping review, curricular content analysis and expert consultation. Setting and participants: A scoping literature review (PubMed until March 2017) informed development of a contemporary framework of HI competency domains for doctors. National training curricula for 71 postgraduate medical specialties were obtained from the UK General Medical Council and were analysed. Seven UK HI experts were consulted regarding findings. Outcomes: The International Medical Informatics Association (IMIA) Recommendations for Biomedical and Health Informatics Education were used to develop a framework of competency domains. The number (maximum 50) of HI competency domains included in each of the 71 UK postgraduate medical specialties was investigated. After expert review, a universal HI competency framework was proposed. Results: A framework of 50 HI competency domains was developed using 21 curricula from a scoping review, curricular content analysis and expert consultation. All 71 UK postgraduate medical curricula documents were mapped across 29 of 50 framework domains; that is, 21 domains were unrepresented. Curricula mapped between 0 (child and adolescent psychiatry and core surgical training) and 16 (chemical pathology and paediatric and perinatal pathology) of the 50 domains (median=7). Expert consultation found that HI competencies should be universal and integrated with existing competencies for UK clinicians and were under-represented in current curricula. Additional universal HI competencies were identified, including information governance and security and secondary use of data. Conclusions: Postgraduate medical education in the UK neglects HI competencies set out by international standards. Key HI competencies need to be urgently integrated into training curricula to prepare doctors for work in increasingly digitised healthcare environments.